Theranos: the Ethics of Innovation and Deception in Healthcare Technology - Edgar Manuel Cambaza (REVES - Revista Relações Sociais)
The case of Theranos, a health technology company founded by Elizabeth Holmes, presents a profound ethical dilemma that exemplifies the consequences of misrepresentation in healthcare innovation. This analysis examines the company's fraudulent claims regarding its blood-testing technology, which promised groundbreaking results using minimal blood samples. Initially lauded for its potential, Theranos attracted significant investment and partnerships before facing growing scrutiny due to internal whistleblower accounts and investigative journalism. The ethical issues at the core of this case involve the deliberate falsification of leadership's technological capabilities, which leads to harm to patients and significant financial losses for investors. The methodology of this study involved a comprehensive review of academic literature identified through Google Scholar, applying inclusion criteria that focused on ethical analysis, corporate leadership, and regulatory oversight. The selected documents were analyzed using Atlas.ti to code critical themes such as corporate misrepresentation, stakeholder rights, and regulatory failures. Utilizing a multi-faceted ethical analysis—incorporating utilitarian, deontological, virtue ethics, and rights-based perspectives—this study explores the failures of corporate leadership in adhering to professional and ethical obligations. It critically evaluates the responses by stakeholders, including actions taken by regulatory bodies and law enforcement, and discusses the lessons learned for the broader health technology sector. The study concludes by recommending more robust internal governance, transparent leadership, and proactive regulatory oversight as essential measures to prevent future ethical lapses in the industry. The analysis contributes to understanding ethics' critical role in maintaining trust and accountability within healthcare innovation.The case of Theranos, a health technology company founded by Elizabeth Holmes, presents a profound ethical dilemma that exemplifies the consequences of misrepresentation in healthcare innovation. This analysis examines the company's fraudulent claims regarding its blood-testing technology, which promised groundbreaking results using minimal blood samples. Initially lauded for its potential, Theranos attracted significant investment and partnerships before facing growing scrutiny due to internal whistleblower accounts and investigative journalism. The ethical issues at the core of this case involve the deliberate falsification of leadership's technological capabilities, which leads to harm to patients and significant financial losses for investors. The methodology of this study involved a comprehensive review of academic literature identified through Google Scholar, applying inclusion criteria that focused on ethical analysis, corporate leadership, and regulatory oversight. The selected documents were analyzed using Atlas.ti to code critical themes such as corporate misrepresentation, stakeholder rights, and regulatory failures. Utilizing a multi-faceted ethical analysis—incorporating utilitarian, deontological, virtue ethics, and rights-based perspectives—this study explores the failures of corporate leadership in adhering to professional and ethical obligations. It critically evaluates the responses by stakeholders, including actions taken by regulatory bodies and law enforcement, and discusses the lessons learned for the broader health technology sector. The study concludes by recommending more robust internal governance, transparent leadership, and proactive regulatory oversight as essential measures to prevent future ethical lapses in the industry. The analysis contributes to understanding ethics' critical role in maintaining trust and accountability within healthcare innovation.